Mental Health and Gratitude in a Community with Social Violence - Vega, Marisela Gutiérrez; Del Villar, Oscar Armando Esparza; Saucedo, Irene Concepción Carrillo; Alvarado, Priscila Montañez (European Scientific Journal, ESJ, 2017)
In recent years, Mexico experienced the violence, fear and terror of a drug-war. Juarez, Mexico is a border town where the highest levels of violence were registered during this war. Violence in all its forms, has been related to poor physical and mental health, therefore some of its manifestations are anxiety, phobias, sadness, depression, hostility, paranoid ideation, among other mental disorders. Positive psychology is a branch of psychology that promotes better quality of life and prevention of metal illnesses through the enhancement of positive emotions and values. Studies have shown when people go through an adverse situation, they still experience positive emotions, such as gratitude. It was the goal of the study to understand psychological distress (such as paranoid ideation, depression, hostility among other psychological problems) and its relationship with gratitude. A group of 315 college students answered the SCL-90-R , a measure of psychological problems, and the Gratitude Questionnaire (GQ-6). Significant and negative correlations between each of the SCL-90-R subscales and gratitude were obtained, that is, as gratitude increases, psychological distress decreases. It can be concluded that positive emotions, particularly gratitude, might improve the way people cope in difficult situations.